Kaiser Julian 'Apostata' und die philosophische Reaktion gegen das Christentum - Schäfer, Christian (Millennium-Studien / Millennium Studies, 2008)
During his short reign in the 4th century, Emperor Julian II, known as the Apostate, attempted to combat Christianity philosophically and to set up a pagan Neo-Platonic doctrine as a counter-programme. The volume presents a collection of papers on the general relationship between Platonism and Christianity, on Julian's character and his philosophical programme and on individual writings in which the Emperor sets out his own position and his critique of Christian thought.